Tasting spoons: Assessing how the material of a spoon affects the taste of the food - Piqueras-Fiszman, B; Laughlin, Z; Miodownik, M; Spence, C (2012)
This study investigated the effect that the taste of certain metals has on the perception of food. Four spoons plated with different metals (gold, copper, zinc, and stainless steel) were used to taste cream samples having different tastes: sweet, sour, bitter, salty, and plain. The results revealed that the zinc and copper spoons, in addition to transferring a somewhat metallic and bitter taste, enhanced to a greater or lesser extent, each cream's dominant taste. Contrary to our expectations, the metallic taste of the copper and zinc spoons did not seem to affect the pleasantness of the samples significantly. These findings reveal that the effect that the metals from which cutlery can be made have on food perception differs from that found when the metal salts are added to the composition of the food itself. © 2011 Elsevier Ltd.